The Revised Inventory of the Dimensions of Emerging Adulthood (IDEA-R) and Substance Use Among College Students. (December 2017) - Allem, Jon-Patrick; Sussman, Steve; Unger, Jennifer B.
Transition-to-adulthood themes, or thoughts and feelings about emerging adulthood, have been measured by the Inventory of the Dimensions of Emerging Adulthood (IDEA) and found to be associated with substance use among emerging adults. It has been suggested, however, that the IDEA is lengthy and may not include the most unique and theoretically relevant constructs of emerging adulthood. The Revised Inventory of the Dimensions of Emerging Adulthood (IDEA-R) was developed as an alternative instrument, but research has yet to determine the relationship between the IDEA-R and substance use among emerging adults (ages 18–25 years). College students completed surveys indicating their identification with transition-to-adulthood themes and substance use. Logistic regression models examined the associations between transition-to-adulthood themes and marijuana use and binge drinking, respectively. Participants who felt emerging adulthood was a time of identity exploration were less likely to report marijuana use, while feelings of experimentation/possibility were positively associated with marijuana use and binge drinking. The IDEA-R may be useful for identifying correlates of substance use among emerging adults. Future research should evaluate the IDEA-R among representative samples of emerging adults to confirm the findings of this study. Health professionals working in substance use prevention may consider targeting the themes of identity exploration and experimentation/possibility in programs intended for emerging adults.